Noninferiority of glucose-6-phosphate dehydrogenase deficiency diagnosis by a point-of-care rapid test vs the laboratory fluorescent spot test demonstrated by copper inhibition in normal human red blood cells. - Baird, J; Dewi, M; Subekti, D; Elyazar, I; Satyagraha, A (2014)
Tens of millions of patients diagnosed with vivax malaria cannot safely receive primaquine therapy against repeated attacks caused by activation of dormant liver stages called hypnozoites. Most of these patients lack access to screening for glucose-6-phosphate dehydrogenase (G6PD) deficiency, a highly prevalent disorder causing serious acute hemolytic anemia with primaquine therapy. We optimized CuCl inhibition of G6PD in normal red blood cells (RBCs) to assess G6PD diagnostic technologies suited to point of care in the impoverished rural tropics. The most widely applied technology for G6PD screening-the fluorescent spot test (FST)-is impractical in that setting. We evaluated a new point-of-care G6PD screening kit (CareStart G6PD, CSG) against FST using graded CuCl treatments to simulate variable hemizygous states, and varying proportions of CuCl-treated RBC suspensions to simulate variable heterozygous states of G6PD deficiency. In experiments double-blinded to CuCl treatment, technicians reading FST and CSG test (n = 269) classified results as positive or negative for deficiency. At G6PD activity ≤40% of normal (n = 112), CSG test was not inferior to FST in detecting G6PD deficiency (P = 0.003), with 96% vs 90% (P = 0.19) sensitivity and 75% and 87% (P = 0.01) specificity, respectively. The CSG test costs less, requires no specialized equipment, laboratory skills, or cold chain for successful application, and performs as well as the FST standard of care for G6PD screening. Such a device may vastly expand access to primaquine therapy and aid in mitigating the very substantial burden of morbidity and mortality imposed by the hypnozoite reservoir of vivax malaria.